STRATEGI PEMBELAJARAN AGAMA HINDU SELAMA PANDEMI COVID-19 - I Gede Dharman Gunawan; Mitro Mitro; Kadek Hengki Primayana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This paper discusses the strategy of learning Hinduism to students in the Covid-19 pandemic. Learning strategy is an activity carried out by teachers and students in the process of changing behavior and science. During the Covid-19 pandemic which influenced the teaching and learning process in the classroom, requiring teachers to change the Hindu learning strategies for students studying online at home. The learning system consists of several components that interact with each other, namely the teacher, students, learning materials, media, methods, and evaluations.